Copy–move forgery detection based on multi‐radius PCET. Issue 2 (1st February 2017) - Wo, Yan; Yang, Kemin; Han, Guoqiang; Chen, Haichao; Wu, Wenbo
Abstract : Copy–move, which copies part of an image and pastes to another part of the same image, is one of the most commonly used image tampering operations. The copied part may suffer to post‐processing operations such as rotation, scaling and blur to make the forgery visually convincing. To detect the copied parts with large‐scale rotation and scaling, this study proposes a copy–move forgery detection method based on multi‐radius polar complex exponential transform (PCET). First, the multi‐radius PCET with graphic processing unit acceleration is used to extract the rotational invariant and multi‐scale features. Then, the lexicographical order matching algorithm, optimised with minimum heap is applied to get a coarse match result. After that, the accurate detection based on radius ratio and position information is used to get the accurate detection result. Compared with the state‐of‐the‐art methods, the proposed method can detect the copied parts with large‐scale rotation or scaling and is robust against Joint Photographic Experts Group (JPEG) compression, smoothing and noise degrading.